Peripheral Neuropathy and Hereditary Tyrosinemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Neurologic crises in 48 children with tyrosinemia identified on neonatal screening since 1970 are described from the Departments of Genetics, Hopital Sainte Justine, Hopital de Chicoutimi; and Universite Laval, Quebec, Canada.